Efek Perasan Kering Kulit Nanas (Ananas comosus (L.) Merr) terhadap Waktu Perdarahan dan Pembekuan Darah pada Tikus Putih Jantan - Veronica Bella Lupita; Opstaria Saptarini; Lina Susanti (Jurnal Farmasi Indonesia, 2015)
Pineapple has a peel that contains bromelain enzyme which is useful as platelet antiagregation. This study was aimed to determine the effect of pineapple peel dried juice on bleeding and clotting time extention, and to know the most effective dose in prolonging bleeding time and blood clotting. This study includes the determination of plants, drying of pineapple peel, the identification of the chemical contents, and test of bleeding and clotting time. This study used 5 treatment groups. The group was divided into treatment groups with pineapple peel dried juice variation dose of 28 mg/200 g BW, 56 mg/200 g BW, and 112 mg/200 g BW, positive control group (acetosal 3.7 mg/200 g BW), and negative control group (distilled water). The identification results showed chemical constituents of bromelain enzyme compounds, flavonoids, and saponins. The test results showed that platelets antiagregation freeze drying product from pineapple peel dried juice which was administered orally could prolong the bleeding time and blood clotting on white male rats. Pineapple peel dried juice with a dose of 112 mg/200 g BW gave the best effect to the extension of bleeding and clotting time with an average increase in bleeding time of 150seconds and an increase in clotting time of 105 seconds.